Long and Winding Road of Molecular Data in Phylogenetic Analysis - Suárez-Díaz, Edna (Journal of the history of biology, 2014)
The use of molecules and reactions as evidence, markers and/or traits for evolutionary processes has a history more than a century long. Molecules have been used in studies of intra-specific variation and studies of similarity among species that do not necessarily result in the analysis of phylogenetic relations. Promoters of the use of molecular data have sustained the need for quantification as the main argument to make use of them. Moreover, quantification has allowed intensive statistical analysis, as a condition and a product of increasing automation. All of these analyses are subject to the methodological anxiety characteristic of a community in search of objectivity (Suárez-Díaz and Anaya-Muñoz, Stud Hist Philos Biol Biomed Sci 39:451–458, 2008). It is in this context that scientists compared and evaluated protein and nucleic acid sequence data with other types of molecular data – including immunological, electrophoretic and hybridization data. This paper argues that by looking at long-term historical processes, such as the use of molecular evidence in evolutionary biology, we gain valuable insights into the history of science. In that sense, it accompanies a growing concern among historians for big-pictures of science that incorporate the fruitful historical research on local cases of the last decades.